Toleransi dan pluralisme di Indonesia - ARIFIN, NINIS FEBRIYANTI (Maliki Interdisciplinary Journal, 2026)
Indonesia is a country with a high level of diversity in religion, ethnicity, culture, and language, making tolerance and pluralism essential foundations for maintaining national unity. The problems faced by Indonesian society include increasing intolerance, radicalism, social polarization, discrimination against minority groups, and the spread of hate speech through digital media. This study aims to analyze tolerance and pluralism in Indonesia, the factors influencing them, the challenges encountered, and the efforts to strengthen them in social life. The research uses a qualitative approach with a literature study method through the analysis of scientific journals, academic articles, and documents related to tolerance and religious moderation. The findings show that tolerance can create social harmony, strengthen social solidarity, and preserve national unity. Multicultural education, social interaction, the culture of mutual cooperation, and religious moderation support the creation of harmonious social life. The development of social media and low digital literacy remain challenges in maintaining pluralism in Indonesia. This study proposes strengthening religious moderation, tolerance education from an early age, improving digital literacy, interfaith dialogue, and law enforcement against acts of intolerance as solutions to build a peaceful, inclusive, and harmonious society.